Context is key: exogenous ketosis and athletic performance - Dearlove, D; Faull, O; Clarke, K (Elsevier, 2019)
Ketone bodies are energetically efficient metabolic substrates, which are synthesised from lipids during prolonged caloric deprivation. Once considered a simple metabolite to fuel the brain during starvation, ketone bodies are now recognised as having pleiotropic effects on metabolism, including modulating the availability and catabolism of other substrates. The combination of improved energetics and fuel sparing observed during ketosis is pivotal to maintaining energy homeostasis during starvation or fasting. Harnessing these actions may also offer a method to enhance human endurance. Owing to the necessity of depleting carbohydrate stores to induce ketogenesis, exercising during an endogenous ketosis is unlikely to be advantageous. In contrast, the delivery of exogenous ketones creates a novel physiological state, where high circulating ketone concentrations and replete carbohydrate stores are present. Here, we discuss the current understanding of how exogenous ketosis may mimic advantageous aspects of starvation physiology and in doing so, be used to enhance human exercise endurance performance.